The Influence of Organizational Culture and Information Technology Capabilities on Organizational Performance Through Organizational Citizenship Behavior (Study at the East Java Provincial Forestry Service) - Mu’minati, Ummul; Khuzaini, Khuzaini; Djawoto, Djawoto (Dinasti Publisher, 2025)
This study examines and analyzes the effect of cultural organization and information technology capability on organizational citizenship behavior and organizational performance at the Forestry Services of East Java province. It also examines and analyzes the effect of organizational culture and information technology capability on organizational performance, as measured by organizational citizenship behavior, at the Forestry Services of East Java province. The study applies quantitatively. Furthermore, the data analysis technique used descriptive statistics with Smart Partial Least Squares. The population consists of 208 managerial employees at the Forestry Services of East Java province. Moreover, the data collection technique used was saturated sampling. The sample consisted of 208 employees from Forestry Services in East Java province. The instrument in the data collection technique was a questionnaire. As a result, it shows that both organizational culture and information technology capability have a significant effect on the organizational citizenship behavior and organizational performance at the Forestry Services in East Java province. Likewise, organizational citizenship behavior has a significant effect on organizational performance at the Forestry Services in East Java province. Similarly, organizational culture and information technology capability have a significant effect on organizational performance through organizational citizenship behavior at the Forestry Services in East Java province, with a significant value less than 0.05%.